2011
DOI: 10.1002/pon.1736
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma knowledge, perception, and awareness in ethnic minorities in Chicago: recommendations regarding education

Abstract: Relevance of melanoma education to ethnic people may be improved by using 'melanoma skin cancer', photographs of early melanoma in people with dark skin, and providing guidance on how to inspect hands and feet for suspicious moles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 28 publications
7
100
1
4
Order By: Relevance
“…As part of this evolution, the original 4 skin types (I-IV), which assessed sun reactivity with standardized questions about the ease of sun burning and tanning reactions to the first exposure in the summer, were modified by adding SPT V and VI to include those with brown and black skin [1] . Our research demonstrated that the modifications to include people with skin of color were neither culturally sensitive nor accurate, as people of color were unable to respond to the questions of sunburn and tanning [20][21][22] . People with deep pigmentation of the skin did not report turning red or pink but rather experienced "irritation" after sun exposure [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this evolution, the original 4 skin types (I-IV), which assessed sun reactivity with standardized questions about the ease of sun burning and tanning reactions to the first exposure in the summer, were modified by adding SPT V and VI to include those with brown and black skin [1] . Our research demonstrated that the modifications to include people with skin of color were neither culturally sensitive nor accurate, as people of color were unable to respond to the questions of sunburn and tanning [20][21][22] . People with deep pigmentation of the skin did not report turning red or pink but rather experienced "irritation" after sun exposure [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Our research demonstrated that the modifications to include people with skin of color were neither culturally sensitive nor accurate, as people of color were unable to respond to the questions of sunburn and tanning [20][21][22] . People with deep pigmentation of the skin did not report turning red or pink but rather experienced "irritation" after sun exposure [20][21][22]. Another limitation of the six Roman numeral Fitzpatrick SPT integers was the reliance upon a history of sunburn after the first exposure of summer.…”
Section: Resultsmentioning
confidence: 99%
“…Drugi primer kvalitativne analize navedene u jednom radu jeste organizacija fokus grupa koje imaju za cilj diskusiju i razradu teme, nakon obavljenog prvog seta ispitivanja učesnika vezano za zdravstvenu pismenost i melanom [10]. Nakon toga podeljene su brošure "Zašto bi trebalo znati o melanomu" u cilju edukacije (tabela 2).…”
Section: Instrumenti Za Kvalitativnu Analizu U Vezi Sa Zdravstvenom Punclassified
“…U dva obrađena rada analizirana su tri pitanja, za koje je zaključeno da su efikasna u otkrivanju neefikasne ili marginalne zdravstvene pismenosti među odraslom populacijom pacijenata [10,13]. Ova tri pitanja su nastala i procenjena na osnovu njihove efikasnosti u identifikaciji pacijenata sa neefikasnom ili marginalnom zdravstvenom pismenošću upoređenom sa S-TOFHLA (kratka verzija, engl.…”
Section: Wwwtmgorgrsunclassified
See 1 more Smart Citation